Brightest cluster galaxies are statistically special from z = 0.3 to z = 1. Issue 3 (17th August 2021) - Dalal, Roohi; Strauss, Michael A; Sunayama, Tomomi; Oguri, Masamune; Lin, Yen-Ting; Huang, Song; Park, Youngsoo; Takada, Masahiro
ABSTRACT: We study brightest cluster galaxies (BCGs) in ∼5000 galaxy clusters from the Hyper Suprime-Cam (HSC) Subaru Strategic Program. The sample is selected over an area of 830 deg 2 and is uniformly distributed in redshift over the range of z = 0.3−1.0. The clusters have stellar masses in the range of 10 11.8 −10 12.9 M⊙ . We compare the stellar mass of the BCGs in each cluster to what we would expect if their masses were drawn from the mass distribution of the other member galaxies of the clusters. The BCGs are found to be 'special', in the sense that they are not consistent with being a statistical extreme of the mass distribution of other cluster galaxies. This result is robust over the full range of cluster stellar masses and redshifts in the sample, indicating that BCGs are special up to a redshift of z = 1.0. However, BCGs with a large separation from the centre of the cluster are found to be consistent with being statistical extremes of the cluster member mass distribution. We discuss the implications of these findings for BCG formation scenarios.